Clopidogrel, a P2Y12 receptor antagonist, potentiates the inflammatory response in a rat model of peptidoglycan polysaccharide-induced arthritis. - Analia E Garcia; Sripal R Mada; Mario C Rico; Raul A Dela Cadena; Satya P Kunapuli (PLoS ONE)
The P2Y12 receptor plays a crucial role in the regulation of platelet activation by several agonists, which is irreversibly antagonized by the active metabolite of clopidogrel, a widely used anti-thrombotic drug. In this study, we investigated whether reduction of platelet reactivity leads to reduced inflammatory responses using a rat model of erosive arthritis. We evaluated the effect of clopidogrel on inflammation in Lewis rats in a peptidoglycan polysaccharide (PG-PS)-induced arthritis model with four groups of rats: 1) untreated, 2) clopidogrel-treated, 3) PG-PS-induced, and 4) PG-PS-induced and clopidogrel-treated. There were significant differences between the PG-PS+clopidogrel group when compared to the PG-PS group including: increased joint diameter and clinical manifestations of inflammation, elevated plasma levels of pro-inflammatory cytokines (IL-1 beta, interferon (IFN) gamma, and IL-6), an elevated neutrophil blood count and an increased circulating platelet count. Plasma levels of IL-10 were significantly lower in the PG-PS+clopidogrel group compared to the PG-PS group. Plasma levels of platelet factor 4 (PF4) were elevated in both the PG-PS and the PG-PS+clopidogrel groups, however PF4 levels showed no difference upon clopidogrel treatment, suggesting that the pro- inflammatory effect of clopidogrel may be due to its action on cells other than platelets. Histology indicated an increase in leukocyte infiltration at the inflammatory area of the joint, increased pannus formation, blood vessel proliferation, subsynovial fibrosis and cartilage erosion upon treatment with clopidogrel in PG-PS-induced arthritis animals. In summary, animals treated with clopidogrel showed a pro-inflammatory effect in the PG-PS-induced arthritis animal model, which might not be mediated by platelets. Elucidation of the mechanism of clopidogrel-induced cell responses is important to understand the role of the P2Y12 receptor in inflammation.